Valuasi Ekonomi Kawali Gecong sebagai Aset Budaya untuk Mendukung Pembangunan Ekonomi Berkelanjutan - Agus Setiawan; Andi Kamilah Zahra; Muhammad Yamin; Tri Aryana; Alamsyah Alamsyah (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the cultural values embodied in kawali gecong and examine its accounting treatment as a heritage asset. The study employed a qualitative interpretive approach using a phenomenological method. Data were collected through in-depth interviews with a kawali gecong owner in Bone Regency and documentation of the perspectives of panre bessi (traditional Bugis blacksmiths) obtained from cultural records and video documentation of the forging process. The findings reveal that kawali gecong embodies historical, symbolic, philosophical, and social values reflected in the concept of siri', intergenerational inheritance, and traditional craftsmanship. These values shape its economic valuation, which is based not on market price but on its sustained social, cultural, educational, and historical benefits. From an accounting perspective, kawali gecong fulfills the characteristics of a heritage asset, with recognition based on service potential, qualitative-descriptive measurement, presentation through systematic heritage asset inventories, and comprehensive disclosure covering its history, cultural significance, and physical condition.